IMPACT OF EXTERNAL SUPPLY CHAIN MANAGEMENT ON FINANCIAL PERFORMANCE OF FIRMS IN THAILAND; WITH THE MEDIATING ROLE OF SUPPLY CHAIN SUSTAINABILITY - Suksod, Pornkul; Pongsiri, Thaniya (International Journal of Supply Chain Management, 2019)
This study aims to provide empirical results about the external management practices in supply chain on the financial performance of manufacturing firms in Thailand. It also emphasizes the mediating role of sustainable supply chain management and its importance while considering the relation between external practices and performance. Quantitative method in the form of questionnaires is adopted in this paper. Using this survey method, the information is collected from the 346 manufacturing firms of Thailand and is then analyzed by using statistical tools such as SPSS and AMOS. The findings clearly depicts that there rely a positive significant relationship between external supply chain practices and firm financial performance. It also positively signifies the intervening role of sustainable efforts among this relationship. It is an extension to literature related to sustainable supply chain management practices and their impact on performance levels of firms. It also help mangers to focus on their external socially responsible supply chain practices to elevate financial performance. This study focuses on the comprehensive supply chain management practices on the manufacturing firms of Thailand. It also elaborate the significance of sustainability and its impact on performance indicators and growth of firms.